2020
DOI: 10.3390/molecules25184046
|View full text |Cite
|
Sign up to set email alerts
|

Flame-Retardant Systems Based on Chitosan and Its Derivatives: State of the Art and Perspectives

Abstract: During the last decade, the utilization of chitin, and in par0ticular its deacetylated form, i.e. chitosan, for flame retardant purposes, has represented quite a novel and interesting application, very far from the established uses of this bio-sourced material. In this context, chitosan is a carbon source that can be successfully exploited, often in combination with intumescent products, in order to provide different polymer systems (namely, bulky materials, fabrics and foams) with high flame retardant (FR) fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(38 citation statements)
references
References 55 publications
0
26
0
Order By: Relevance
“…Nano-TiO 2 particles added into the chitosan coating cooled the pyrolysis region on the fabric surface with a synergetic effect and caused endothermic degradation. 16,19 Chitosan contains nitrogen in its structure. In combustion reactions, nitrogen does not give off heat and reacts by taking heat.…”
Section: Smentioning
confidence: 99%
See 2 more Smart Citations
“…Nano-TiO 2 particles added into the chitosan coating cooled the pyrolysis region on the fabric surface with a synergetic effect and caused endothermic degradation. 16,19 Chitosan contains nitrogen in its structure. In combustion reactions, nitrogen does not give off heat and reacts by taking heat.…”
Section: Smentioning
confidence: 99%
“…Research over the last decade has shown that some biological macromolecules and bio-origin products can be used to design “green” and effective flame retardants 16 Therefore, studies have focused on green biocomposites. 17 Chitosan, a green biopolymer, is preferred for surface modification in textile processes due to its cationic structure, unique biological properties and low cost.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chitosan and its derivatives [ 56 ] have been used in several biomedical and pharmaceutical applications, and also as textile and in wastewater treatments. Between one third and one half of the world food production is not consumed [ 57 , 58 ].…”
Section: Sustainable Materials Developed By the Instm Consortiummentioning
confidence: 99%
“…Though CH has recently enjoyed tremendous popularity as a flame retardant, its matrix, chitin, has not attracted enough attention in the field of fire science. Chitin is also a key polysaccharide and the second most important natural polymer in the world after cellulose, and is mainly extracted from crab and shrimp shells [30]. Once chitin suffers a deacetylation process, CH is obtained.…”
Section: Introductionmentioning
confidence: 99%